Extracelulární matrix a umělá plicní ventilace u zdravých plic - zpět k barotraumatu či volumotraumatu? - Pelosi, Paolo; Negrini, Daniela (Current Opinion in Critical Care (České vyd.), 2008)
The extracellular matrix plays an important role in the biomechanical behaviour of the lung parenchyma. The matrix is composed of a three-dimensional fibre mesh filled with different macromolecules, including proteoglycans which have important functions in many lung pathophysiological processes, as they regulate tissue hydration, macromolecular structure and function, response to inflammatory agents, and tissue repair and remodelling. The aim of this review is to describe the role of mechanical ventilation on pulmonary extracellular matrix structure and function. RECENT FINDINGS: Recent experimental and clinical data suggest that in healthy lungs, mechanical ventilation with tidal volume ranging between 7 and 12 ml/kg in the absence of positive end-expiratory pressure may lead to endothelial, extracellular matrix and peripheral airways damage without major inflammatory response. Several mechanisms may explain damage to the lung structure induced by mechanical ventilation: regional overdistension, 'low lung volume' associated with tidal airway closure, and inactivation of surfactant. SUMMARY: Tidal volume reduction to 6 ml/kg may be useful during mechanical ventilation of healthy lungs. The study of the extracellular matrix may be useful to better understand the pathophysiology of ventilator-induced lung injury in healthy and diseased lungs.
Keywords: plíce; Respiratory Distress Syndrome; Humans; zvířata; proteoglykany; Clinical Trials as Topic; klinické zkoušky jako téma; extracelulární matrix; Lung; Positive-Pressure Respiration; Proteoglycans; umělé dýchání; Respiration, Artificial; Animals; Extracellular Matrix; lidé; Tidal Volume; ventilace umělá s výdechovým přetlakem; syndrom dechové tísně; dechový objem; Barotrauma; barotrauma